2015
DOI: 10.1039/c4nr07510b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoluminescence from single nitrogen-vacancy defects in nanodiamonds coated with phenol-ionic complexes

Abstract: Fluorescent nanodiamonds are attracting major attention in the field of bio-sensing and biolabeling. In this work we demonstrate a robust approach to surface functionalize individual nanodiamonds with metal-phenolic networks that enhance the photoluminescence from single nitrogen vacancy (NV) centers. We show that single NV centres in the coated nanodiamonds also exhibit shorter lifetimes, opening another channel for high resolution sensing. We propose that the nanodiamond encapsulation suppresses the non-radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…with permission from PCCP Owner Societies.Various other nanomaterials can also be coated with MPNs. For example, the photoluminescence from single nitrogen-vacancy defects in nanodiamonds is significantly enhanced by MPN coatings[19]. The fluorescence lifetime of the MPN-coated nanodiamonds becomes shorter (τ = 5.5 ± 1.5 ns) than those for uncoated nanodiamonds (τ =8.3 ± 1.1 ns), with the shorter fluorescence lifetime associated with brighter fluorescence.…”
mentioning
confidence: 99%
“…with permission from PCCP Owner Societies.Various other nanomaterials can also be coated with MPNs. For example, the photoluminescence from single nitrogen-vacancy defects in nanodiamonds is significantly enhanced by MPN coatings[19]. The fluorescence lifetime of the MPN-coated nanodiamonds becomes shorter (τ = 5.5 ± 1.5 ns) than those for uncoated nanodiamonds (τ =8.3 ± 1.1 ns), with the shorter fluorescence lifetime associated with brighter fluorescence.…”
mentioning
confidence: 99%
“…17,18 Nonetheless, the ODMR technique is challenging due to the long radiative lifetime and low collection efficiency of photons emitted by the NV centres. [19][20][21] An efficient approach to overcome this issue is by coupling the ND emission to plasmonic modes. [22][23][24] In particular, coupling the readout of the electron spins of NV centres in NDs to plasmonic modes can be employed for realizing on-chip quantum information processing where the plasmonic waveguides can be used as networks to guide, process and transfer the spin quantum information along chipscale devices.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, encapsulation of individual NDs with phenol-ionic complexes leads to enhanced photoluminescence from the ND defects. [9] Our prior studies with polypyrrole (PPy) organic dye showed experimentally that composites of hydrogenated and oxidized detonation nanodiamonds (DNDs) with PPy were successfully fabricated and evince promising properties for photovoltaic applications. [10] Suitability of PPy for photovoltaic applications was also supported by an observed transfer of photogenerated charge between the bulk diamond and PPy observed by Kelvin force microscopy and optical spectroscopy.…”
Section: Introductionmentioning
confidence: 99%